A Quadrature-Based Tunable Radio-Frequency Sensor for the Detection and Analysis of Aqueous Solutions - Cui, Yan (2014)
A highly tunable and sensitive radio-frequency (RF) sensor is presented for the measurement of aqueous-solution dielectric properties. Two quadrature hybrids are utilized to achieve destructive interference that eliminates the probing signals at both measurement ports. As a result, weak signals of material-under-test (MUT) are elevated for high sensitivity detections at different frequencies. The sensor is demonstrated through measuring 2-propanol-water solution permittivity at 0.01 mole fraction concentration level from ~4 GHz to ~12 GHz. De-ionized water and methanol-water solution are used to calibrate the sensor for quantitative MUT analysis through our proposed model. Micro-meter coplanar waveguides (CPW) are fabricated as RF sensing electrodes. A polydimethylsiloxane (PDMS) microfluidic channel is employed to introduce 250 nL liquid, of which ~1 nL is effectively the MUT. The permittivity and the relaxation time of 2-propanol-water solution are obtained. Compared with our power divider based sensors, the differential reflection coefficients in this work provide additional information that complements the transmission coefficient methods.